Youth engagement in Singapore: the interplay of social and traditional media - Skoric, Marko M. (2013)
This research examines the implications of social media use for political engagement among young people in Singapore. The project included a qualitative analysis of a student protest, followed by a national survey of young Singaporeans. The findings suggest that social media use is positively related to traditional political participation, while also providing evidence of the continued importance of traditional media for political engagement. More specifically, we find that the attention paid to news in traditional media is a more important predictor of both traditional and online participation than the generic use of Facebook.